Ethical disaster or natural disaster? Importance of ethical issue in disaster management - Aung, Khin Thandar; Abdul Rahman, Nurul 'Inayati; Nurumal, Mohd. Said; Ahayalimudin, Nurul'Ain (IOSR journals, 2017)
Background:Since modern disasters, natural or human-made occur more frequently, causing more deaths, affecting more people and increasing economic loss. This becomes making difficult on healthcare system and personnel while assisting and ensuring the lives of the disaster population because of lack of medical resources in conjunction with a mass casualty situation,that can present specific ethical challenges in disaster management. Understanding the nature of the ethical challenges specific to disaster settings is becoming more important to prevent ethical conflicts are to be helpful to all parties to find the least negative option for action under severe conditions. Objective and Method: The purpose of this paper is to describe the importance of ethics in disastermanagement.The reviewed literature for this paper was based onthe related data sources ofethics of disaster management, extensive review ethics and disaster medicine, public health and disasters in CINAL plus, Google scholar and research gate. Discussions: This paper will discussabout theauthorized person who can make ethical decisions in disaster,the ways of making ethical decision and the principles and values that guide on ethical decision making in disaster. Conclusion:As Ethical decision making in disaster cannot be carried out by any one person or community.It requires open discussion and a commitment between the experiences and perspectives of those who are different in the community. Mutual critique will lead to a more adequate ethical foundation in guiding our action in the management of disasters.